2020
DOI: 10.34172/apb.2020.077
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes in Colorectal Cancer Cells upon Treatment with Avicequinone B

Abstract: Purpose: Naphtho[2,3-b]furan-4,9-dione (Avicequinone B), a natural naphthoquinone isolated from the mangrove tree Avicennia alba, is recognized as a valuable synthetic precursor with anti-proliferative effect. However, the molecular mechanism involved in its bioactivity has not been investigated. This study aimed to determine the selectivity of avicequinone B against cancer cells and the transcriptomic changes induced in colorectal cancer (CRC). Methods: The cytotoxic effect against adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The naphthoquinone 119 (Figure 13 ) from the mangrove tree Avicennia alba reduced the viability of human breast, colorectal, and lung adenocarcinoma cells (EC 50 = 3–12 µM). 389 Transcriptome analysis revealed that 119 regulates ferroptosis‐related genes (e.g., SLC7A11 and GCL), however, in the opposite direction as expected for ferroptosis induction. The authors speculate about unknown targets and feedback mechanisms.…”
Section: Ferroptosis‐inducing Natural Products With Diverse Mechanismsmentioning
confidence: 94%
See 2 more Smart Citations
“…The naphthoquinone 119 (Figure 13 ) from the mangrove tree Avicennia alba reduced the viability of human breast, colorectal, and lung adenocarcinoma cells (EC 50 = 3–12 µM). 389 Transcriptome analysis revealed that 119 regulates ferroptosis‐related genes (e.g., SLC7A11 and GCL), however, in the opposite direction as expected for ferroptosis induction. The authors speculate about unknown targets and feedback mechanisms.…”
Section: Ferroptosis‐inducing Natural Products With Diverse Mechanismsmentioning
confidence: 94%
“…The authors speculate about unknown targets and feedback mechanisms. 389 9.4.10 | Gallic acid (120) 3,4,5-Trihydroxybenzoic acid (120; Figure 13) is prevalent in Quercus species and has recently been proposed to induce ferroptosis besides apoptosis and necroptosis at high concentrations (300 µM) in human HeLa epithelial adenocarcinoma cells, H446 lung carcinoma epithelial cells, SH-SY5Y neuroblastoma cells, MDA-MB-231 breast cancer cells and A375 melanoma cancer cells. 390,391 The contribution of ferroptosis to cell death induction remains enigmatic.…”
Section: Vitamin C (114)mentioning
confidence: 99%
See 1 more Smart Citation
“…Modern research into the medicinal effects of plant substances uses the latest technologies and analytical techniques, and the traditional use of medicinal plants is supported by multidirectional scientific research. New substances present in raw plants are constantly being discovered, which may be of importance in medicine because of their great potential to destroy microorganisms or because of their antioxidant and anticancer properties [30].…”
Section: Antifungal Activity Of Substances Derived From Plantsmentioning
confidence: 99%